2018
DOI: 10.2147/ceor.s157606
|View full text |Cite
|
Sign up to set email alerts
|

Cost utility, budget impact, and scenario analysis of racecadotril in addition to oral rehydration for acute diarrhea in children in Malaysia

Abstract: ObjectiveTo perform cost utility (CU) and budget impact (BI) analyses augmented by scenario analyses of critical model structure components to evaluate racecadotril as adjuvant to oral rehydration solution (ORS) for children under 5 years with acute diarrhea in Malaysia.MethodsA CU model was adapted to evaluate racecadotril plus ORS vs ORS alone for acute diarrhea in children younger than 5 years from a Malaysian public payer’s perspective. A bespoke BI analysis was undertaken in addition to detailed scenario … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Thirty studies (47%) were partial economic evaluations which included cost-consequence, cost-minimization, and budget impact analyses, while the full economic evaluations consisted of 17 CEAs 41-57 and 17 CUAs. [58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73] The number of published economic evaluations in Malaysia has increased considerably in the past five years (Figure 2). In 2017, 15 economic evaluations from Malaysia were published total; as of April 2018, 8 studies have been published so far.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty studies (47%) were partial economic evaluations which included cost-consequence, cost-minimization, and budget impact analyses, while the full economic evaluations consisted of 17 CEAs 41-57 and 17 CUAs. [58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73] The number of published economic evaluations in Malaysia has increased considerably in the past five years (Figure 2). In 2017, 15 economic evaluations from Malaysia were published total; as of April 2018, 8 studies have been published so far.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, a study from Malaysia claimed that ORS combined with racecadotril was more effective and costeffective than ORS alone. 7 Similarly, Sreeni vas et al indicated a noticeable reduction in stool frequency at 48 hours and reduced time for recovery with racecadotril use. 9 However, it is worth noting that these studies were conducted in different populations, and regional variations in response to treatment may play a role.…”
Section: Discussionmentioning
confidence: 95%
“…While racecadotril has been employed in developed countries, its incorporation into guidelines for routine use in children with acute diarrhoea is yet to be definitively established. 8 According to a study conducted in Malaysia, the combination of ORS and racecadotril is reported to be more advantageous and cost-effective than using ORS alone 7 . Additionally, Sreeni vas et al observed a significant 34.1% reduction in stool frequency at 48 hours.…”
Section: Introductionmentioning
confidence: 99%
“…As stated before, the mainstay treatment of AGE is ORS. Three cost-efficacy analyses performed on available data from UK, Thailand, and Malaysia showed that the addition of racecadotril to ORS is more cost-efficient than ORS treatment alone, leading to savings to the health care systems up to 900 Euros/patient (21)(22)(23).…”
Section: Cost-efficacy Analysismentioning
confidence: 99%